2015
DOI: 10.1159/000430299
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme Oxygenase-1 by Sodium 9-Hydroxyltanshinone IIA Sulfonate Derivative Contributes to Inhibit LPS-Mediated Inflammatory Response in Macrophages

Abstract: Background/Aim: Sodium 9-acetoxyltanshinone IIA sulfonate (ZY-1A4), a novel compound derived from sodium 9-hydroxyltanshinone IIA sulfonate, was synthesized with potential biological activities. This study aimed to explore the effects of ZY-1A4 on lipopolysaccharide (LPS)-triggered inflammatory response and the underlying mechanisms. Methods: Activation of RAW264.7 macrophages was induced by LPS. The effects of ZY-1A4 on inducible nitric oxide synthase (iNOS) expression, nitric oxide (NO) generation, nuclear f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…A study by Liu et al33 showed that LPS stimulates RAW264.7 macrophages to produce inflammatory reaction and release of inflammatory factors such as inducible nitric oxide synthase (iNOS) and nitric oxide (NO): These changes could be inhibited by administering HO-1 siRNA or PI3K inhibitor LY294002, and these are related to the inhibition of NF-κB activity. This suggested that the expression of HO-1 is closely related to the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Liu et al33 showed that LPS stimulates RAW264.7 macrophages to produce inflammatory reaction and release of inflammatory factors such as inducible nitric oxide synthase (iNOS) and nitric oxide (NO): These changes could be inhibited by administering HO-1 siRNA or PI3K inhibitor LY294002, and these are related to the inhibition of NF-κB activity. This suggested that the expression of HO-1 is closely related to the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The control of HO-1 expression occurs primarily at the transcriptional level [34,35] and Nrf2 is one of the most potent transcriptional activators of HO-1. Induction requires Nrf2 nuclear translocation and binding to the antioxidant response element (ARE) controlling expression of HO-1 as well as other phase II antioxidant and stress-inducible genes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, STS has been used in China to treat patients with angina pectoris and coronary artery diseases for many years . To accommodate the cardiovascular protective effects of STS, a novel derivative (ZY‐1A4, introducing an –acetoxyl group at C1) was synthesized and biologically evaluated to test its anti‐inflammatory effects . Mechanistic studies in cultured mouse macrophages revealed that ZY‐1A4 exhibited potent inhibitory effects on LPS‐induced iNOS‐dependent NO production by repressing NF‐ƙB activation and activating anti‐oxidant NRF2/HO‐1 signaling pathway .…”
Section: Structure–activity Relationship Of Tanshinonesmentioning
confidence: 99%
“…166 Mechanistic studies in cultured mouse macrophages revealed that ZY-1A4 exhibited potent inhibitory effects on LPS-induced iNOS-dependent NO production by repressing NF-ƙB activation and activating anti-oxidant NRF2/HO-1 signaling pathway. 166 The potent anti-inflammatory profile of ZY-1A4 indicates that the introduction of the hydrophilic sodium sulfonate and acetoxyl moieties could potentially increase the oral bioavailability and anti-atherosclerotic efficacy of TSN. Interestingly, CTS, with a chemical structure very close to TSN, shows no significant inhibition on macrophage-derived foam cell formation, 167 but displays increased anti-inflammatory effects on LPS-stimulated NO production (IC 50 = 8 μM for TSN, 1.5 μM for CTS).…”
Section: Structure-activity Relationship Of Tanshinonesmentioning
confidence: 99%